Clinically meaningful classes of financial toxicity for patients with diabetes - Minal R. Patel; Jonathan P. Troost; Michele Heisler; Noelle E. Carlozzi (Journal of Patient-Reported Outcomes)
Abstract Aims This study aims to improve the interpretability and clinical utility of the COmprehensive Score for financial Toxicity-Functional Assessment of Chronic Illness Therapy (COST-FACIT) by identifying distinct financial toxicity classes in adults with diabetes. Methods Data included a sample of 600 adults with Type 1 or Type 2 diabetes and high A1c. Latent Class Analysis was used to identify subgroups of patients based on COST-FACIT score patterns. Results We identified 3 financial toxicity classes (high, medium and low) with strong indicators of membership classification. Multiple indicators of financial stress, maladaptive cost-coping behaviors, more comorbidities, more prescribed medications, more diabetes distress, more depressive symptoms, closer to the federal poverty level, female, having lower educational attainment and being single were all significant predictors of high financial toxicity class membership. A score of 26 on the COST-FACIT was the strongest threshold for sorting high vs. medium/low financial toxicity, with a positive predictive value (PPV) of 76% and negative predictive value (NPV) of 93%. Conclusion The COST-FACIT can be used to reliably identify people with diabetes that have high financial toxicity. Integrating this new cut-score into clinical practice may help clinical teams identify people in need of additional support due to financial toxicity.